Investigating the Association Between a Risk-Directed Prophylaxis Protocol and Postoperative Nausea and Vomiting: Validation in a Low-Income Setting. (12th October 2022) - Tuyishime, Jean de Dieu H.; Niyitegeka, Joseph; Olufolabi, Adeyemi J.; Powers, Samuel; Naik, Bhiken I.; Tsang, Siny; Durieux, Marcel E.; Twagirumugabe, Theogene
Abstract : BACKGROUND: The efficacy of postoperative nausea and vomiting (PONV) prevention protocols in low-income countries is not well known. Different surgical procedures, available medications, and co-occurring diseases imply that existing protocols may need validation in these settings. We assessed the association of a risk-directed PONV prevention protocol on the incidence of PONV and short-term surgical outcomes in a teaching hospital in Rwanda. METHODS: We compared the incidence of PONV during the first 48 hours postoperatively before (April 1, 2019–June 30, 2019; preintervention) and immediately after (July 1, 2019–September 30, 2019; postintervention) implementing an Apfel score-based PONV prevention strategy in 116 adult patients undergoing elective open abdominal surgery at Kigali University Teaching Hospital in Rwanda. Secondary outcomes included time to first oral intake, hospital length of stay, and rate of wound dehiscence. Interrupted time series analyses were performed to assess the associated temporal slopes of the outcome before and immediately after implementation of the risk-directed PONV prevention protocol. RESULTS: Compared to just before the intervention, there was no change in the odds of PONV at the beginning of the postintervention period (odds ratio [OR], 0.23; 95% confidence interval [CI], 0.05–1.01). There was a decreasing trend in the odds of nausea (OR, 0.60; 95% CI, 0.36–0.97) per month. However, there was no difference in the incidence of nausea immediately after implementation of the protocol (OR, 0.96; 95% CI, 0.25–3.72) or in the slope between preintervention and postintervention periods (OR, 1.48; 95% CI, 0.60–3.65). In contrast, there was no change in the odds of vomiting during the preintervention period (OR, 1.01; 95% CI, 0.61–1.67) per month. The odds of vomiting decreased at the beginning of the postintervention period compared to just before (OR, 0.10; 95% CI, 0.02–0.47; P = .004). Finally, there was a significant decrease in the average time to first oral intake (estimated 14 hours less; 95% CI, −25 to −3) when the protocol was first implemented, after adjusting for confounders; however, there was no difference in the slope of the average time to first oral intake between the 2 periods ( P = .44). CONCLUSIONS: A risk-directed PONV prophylaxis protocol was associated with reduced vomiting and time to first oral intake after implementation. There was no substantial difference in the slopes of vomiting incidence and time to first oral intake before and after implementation.